The influence of social media of Universitas Negeri Yogyakarta Gunungkidul Campus to create brand image on student decision making - Anugerah Tesa Aulia; Ignatius Agung Satyawan; Albert Muhammad Isrun Naini (Universitas Negeri Yogyakarta, 2022)
In 2020, Universitas Negeri Yogyakarta (UNY) opened a new vocational campus in Gunungkidul Regency. The Socialization of UNY Gunungkidul campus by the admission department cannot be performed face-to-face due to the Covid-19 pandemic. Therefore, UNY Gunungkidul Campus socializes the enrollment programs via online mode. The opening of the campus aims to equalize and improve the quality of high school education in Yogyakarta. Gunungkidul is the regency with the second highest number of poor people in Yogyakarta. UNY Gunungkidul Campus utilizes social media as a promotional media to support the formation of a brand image for student decision making. This study employed a descriptive quantitative approach using a Likert scale measurement. The population in the study was 502 students. The samples were calculated using the Albert Harkin Colton table formulation which obtained 90 respondents. This analysis utilized SPSS 16 software. The results of this study show that 64.5% of 2020 student decision making is influenced by social media, although the promotion is still centered on the UNY Official account.